CEO SUCCESSION AND STOCKHOLDER REACTION: THE INFLUENCE OF ORGANIZATIONAL CONTEXT AND EVENT CONTENT. - FRIEDMAN, S. D.; SINGH, H. (Academy of Management Journal, 1989)
In this article, we construe chief executive officer (CEO) succession events as instances of organizational change. Predictions of positive, negative, or inconsequential outcomes of succession events are contingent on two features of organizational context-presuccession organizational performance and organizational size-and three elements of the content of a succession event: the force initiating the change in CEO, the predecessor's disposition, and the origin of the new CEO. We found that poor presuccession performance was associated with boardinitiation and predecessor departure. Stockholder reactions were positive when presuccession performance was poor and either boards or, to a lesser extent, CEOs initiated successions. Successions that occurred when performance had been good resulted in negative consequences, as did those caused by CEO disability. However, most successions studied were customary retirements associated with no significant stockholder reaction. CEO succession events are of central concern in organization theory. They are universal-if organizations survive long enough, they must experience succession-and they have provided a means for assessing the efficacy of leaders in shaping organizational fortunes by demarcating eras of stewardship. After some decades of research, however, scholars have not reached consensus on the general question of whether leaders make a difference. Instead, the literature on succession has led to a focus on specifying conditions under which it is more or less possible for individuals newly placed in the seat of legitimate authority to influence important organizational outcomes. Under certain circumstances, new CEOs can have palpable effects on